Sediment consolidation in ephemeral river: the effect of applied loading on soil properties and dredging method selection. Issue 3 (3rd July 2021) - Soemitro, R. A. A.; Adriati, F.; Warnana, D. D.; Mukunoki, T.; Soetanto, R.; Maulana, M. A.
ABSTRACT: Bengawan Solo River, a typical large ephemeral river in Indonesia, is facing stream problems induced by the erosion and deposition of sediment. Imbalance between these two phenomena on the riverbed can lead to excessive sedimentation, increased risk of flooding, and formation of sandbars. One proposed solution to address this problem is dredging. However, this process can have potential negative effects on the environment, such as removal or destruction of the biota in the dredged materials, increased turbidity, as well as coverage of the benthos in the vicinity. Also, different dredging methods are needed to suit sediments with different properties. Therefore, the knowledge of the deposited sediment properties is required so that appropriate methods can be selected. The sediment characteristics were obtained by performing laboratory tests on physical and consolidation properties and shear strength tests of a soil sample. The results indicate that the materials were broadly grouped into sandy sediment in downstream areas and clayey sediment in estuary areas. The distribution of sediment properties varies with depth because of subsequent erosion and deposition over time. Additionally, the distribution also shows that sand content decreases as the origin of sample approaches estuary areas. Erosion is predominant at locations with small hydraulic radius and high flow velocity, mostly at downstream areas, whereas deposition is predominant at locations with a large hydraulic radius and low flow velocity, specifically at estuary areas. The shear strength increases as the loads imposed by the self-weight of sediment layer increase. The analysis suggests that sediments cannot be eroded naturally as they have a shear strength that exceeds the small-capacity dredging method ( τ > 20 k P a ); therefore, the removal of excess sediment in such areas requires dredging methods of larger capacities (such as grab dredger).